RECONSTRUCTION OF DESTROYED HOUSING - Dena Karim-Sultanovich Bataev; Khalid Abubakarovich Paytaev (Вестник Северо-Кавказского федерального университета)
The article assesses the state of the housing fund of the Russian Federation and the Chechen Republic in particular, we analyze the results of the authorities of the Chechen Republic on the repair and restoration of damaged housing, the problem questions on the management of repair and restoration of damaged housing, examines the role of the state in managing the repair and restoration of damaged housing Fund.